اثر استخدام دورة التعلم في تحصیل طالبات مرحلة الرابع العام للمعلومات الفیزیائیة واستبقائھا (Journal of the College of Education for Women, 2019)
This research aims to reveal the impact of applying a teaching course ingaining and preserving information by female students comparing with thetraditional method, through testing the two following hypotheses:1. There is no difference with statistical significance at the level ofsignificance (0.05) between the average grades achieved by theexperimental group of female students taught using a teaching course,and the control group of female students taught using the traditionalmethod.2. There is no difference with statistical significance at the level ofsignificance (0.05) between the average grades achieved by theexperimental group of female students taught using a teaching course,and the control group of female students taught using the traditionalmethod, when repeating the test after a specific period of time.For this purpose, we applied a field experiment on two female studentsgroups (experimental group and control group) after preparing all itsrequirements and tools. Through the experiment, the two abovementionedhypotheses were investigated and revealed that the teaching course helpunderstand and comprehend the scientific concepts which lead to an increasein female student's grades and improve the student's scientific investigation aswell . Because this course helped organize the contents and clarify themeaning and relations which simplify the student's comprehension. Moreover,to contact the new knowledge and whatever preserved information they have.According to the abovementioned conclusions, the researcher providedsome fruitful suggestions.